RETRACTED: Emotional intelligence as the production basis of management personnel - Shokhnekh Amira; Mushketova Natalia; Marusinina Elena; Shokhnekh Anna (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001